Performance and characteristics of blend polymer electrolytes based on lithium triflate impregnated potato starch-graphene oxide with ionic liquid as plasticizer / Alyaa Amalina Mohd Azli - Alyaa Amalina , Mohd Azli (2022)
Potato starch (PS)-graphene oxide (GO) blend based solid polymer electrolytes have been developed using lithium triflate (LiCF3SO3) as ionic source via solution casting technique. Lithium based electrolyte system (PS-GO-LiCF3SO3) is further added with ionic liquid, 1-Butyl-3-methylimidazolium chloride ([Bmim][Cl]) as plasticizer to form PS-GO-LiCF3SO3-[Bmim][Cl] electrolyte with better conductivity characteristic. From X-ray diffraction (XRD) analysis, the best ratio of electrolyte composition is found to be 80 wt.% PS : 20 wt.% GO : 40 wt.% LiCF3SO3 : 30 wt.% [Bmim][Cl] with the highest conductivity value of (4.48 ± 0.85) × 10-4 S cm-1. Analysis on temperature dependence conductivity reveals that all electrolytes follow Arrhenius rule. The possible interactions within electrolyte material are verified via Fourier transform infrared spectroscopy (FTIR). Results from field emission scanning electron microscopy (FESEM) have strengthened the conductivity patterns of electrolytes. Data obtained from linear sweep voltammetry (LSV) shows that PS-GO-LiCF3SO3- [Bmim][Cl] electrolyte is electrochemically stable up to 1.92 V and suitable to be used in electrochemical double-layer capacitor (EDLC) application. Specific capacitance, Cs value calculated from galvanosatic charge-discharge measurement has been supported with cyclic voltammetry (CV) analysis. The value of Cs obtained for PS-GO-LiCF3SO3- [Bmim][Cl] EDLC is 37.9 F g−1 at 0.6 mA cm-2 current density.